Perbandingan kinerja keuangan bank konvensional dan bank syariah dengan pendekatan rgec (risk proile, good corporate governance, earnings, capital) - Amalia Sholikhah; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study was to examine the financial performance of conventional bank and Islamic bank on Risk Profile factor, to know about the financial performance of conventional bank and Islamic bank on Good Corporate Governance factor, to know about the financial performance of conventional bank and Islamic bank on Earnings factor, and to know about the financial performance of convensional bank and Islamic bank on Capital factor. The analysis used is normality test and hypothesis test using Independent t-Test. The research sample which used is the banking companies listed in Indonesian Bank (BI) period 2014-2015. Collection research data using purposive sampling method. Data obtained amounted to 48 banks in the period 2014-2015. This research uses analysis used normality test and hypothesis test using Independent t-Test. The result of this study and the discussion show that there is a difference in financial performance in the NPL, LDR, GCG, ROA, and CAR ratio between conventional bank and Islamic bank. Conventional bank have NPL, LDR, and ROA rasio better than Islamic bank while GCG and CAR rasio of Islamic bank is better than conventional bank.